Sistem Informasi Penjualan Mobil Bekas Berbasis Web Mobile pada Showroom Mobil Sinar Terang Lampung Utara - Achmad Ridho Winata; M.Abu Jihad Plaza R (Jurnal Sintaks Logika, 2026)
The high market demand for used cars has driven the need for an efficient and easily accessible management and sales system, considering that the Sinar Terang Car Showroom in North Lampung still relies on conventional methods that often hinder service and information accuracy. This study aims to develop a Mobile Web-Based Used Car Sales Information System to improve operational efficiency and expand promotional reach. The development method chosen is Rapid Application Development (RAD) to quickly produce a functional system. Data collection was conducted through direct observation, in-depth interviews with showroom staff, and literature studies to support the theoretical framework. The result is the implementation of a mobile web-based system that facilitates inventory management, displays car details transparently, and provides direct contact with the showroom. This system has proven to be functional and feasible to use, potentially increasing staff work efficiency and significantly expanding the potential reach of potential customers.